It's a wonderful knife - Wenger, Christine Anne, 1952- (Wenger, Christine Anne, 1952- Comfort food mystery., 2016)
All Trixie Matkowski wants for Christmas is a break-just not the broken leg she got after slipping on some ice. With Sandy Harbor alive in the hustle and bustle of the season, it's the busiest time of the year at Trixie's Silver Bullet Diner. There are millions of things to do, including cater the town's annual Christmas pageant and community dinner with some delicious holiday comfort food.